CESARINO, Pedro de Niemeyer. Oniska: Poética do Xamanismo na Amazônia, São Paulo, Perspectiva/Fapesp, 2011, 423 pp. - Lacerda, Izomar (Revista de Antropologia, 2012)
CESARINO, Pedro de Niemeyer. Oniska: Poética do Xamanismo na Amazônia, São Paulo, Perspectiva/Fapesp, 2011, 423 pp.